I'm traveling alone [large type] - Bjørk, Samuel (Wheeler Publishing, 2016)
International bestseller Samuel Bjørk makes his US debut with a chilling and fast-paced thriller in which two detectives must hunt down a revenge-driven and ruthlessly intelligent killer, and uncover the secret that ties each of them to the crime as I'm Traveling Alone races to an explosive -- and shocking -- conclusion.